Clinical and molecular characteristics of Klebsiella pneumoniae ventilator-associated pneumonia in mainland China. Issue 1 (December 2016) - Guo, Si; Xu, JingJing; Wei, YanShuan; Xu, JunHong; Li, Yi; Xue, Rui
Abstract Background Klebsiella pneumoniae is a prominent nosocomial pathogen that accounts for up to 10 % of all hospital-acquired infections. It is a frequent cause of ventilator-associated pneumonia (VAP). The purpose of this study was to investigate the clinical characteristics ofK. pneumoniae- associated VAP and the molecular characteristics ofK. pneumoniae strains. Methods We retrospectively reviewed 70 mechanically ventilated patients withK. pneumoniae isolated. AllK. pneumoniae strains were examined to determine hypermucoviscosity (HV) phenotype, capsular serotypes, virulence genes, multilocus sequence typing and antimicrobial susceptibility. Results Hypermucoviscosity was found in 14 of 70 (20 %) isolates ofK. pneumoniae . Among the 70 patients, 43 cases (61.4 %) developed VAP. Furthermore, VAP was more frequently induced by HV-positiveK. pneumoniae (14/14, 100 %) than by HV-negative strains (29/56, 51.7 %). HV-positiveK. pneumoniae- associated VAP patients were more inclined to develop bacteremia and had a higher mortality rate than HV-negative strains VAP patients. Antibiotic resistance was more frequent in HV- negative strains- than in HV- positive strains-infected patients. The prevalence ofrmpA and aerobactin genes were 85.7 % and 85.7 % respectively, and serotypes K1 and K2 accounted for 14.3 % and 28.6 % of the hypermucoviscosity strains, respectively. Strains carryingrmpA and aerobactin genes were significantly associated with HV-phenotype, andrmpA and aerobactin coexisted in HV-positive strains. Multilocus sequence typing analysis identified 24 different sequence types fromK. pneumoniae VAP samples. Conclusions HV-phenotype is the major virulence determinant for mechanically ventilated patients. There was a specific sequence typing (ST) distribution between HV-positive and HV-negative strains.